S101 A comparison of the imaging features of early stage primary lung cancer in patients treated with surgery, sabr and microwave ablation. (15th November 2017) - Talwar, A; Jenko, N; Sarim, M; Enescu, M; Whybra, P; Willaime, JMY; Pickup, LC; Hickes, W; Gooding, M; Boukerroui, D; Rahman, NM; Kadir, T; et al.
Abstract : Introduction: Stereotactic Ablative Radiotherapy (SABR) and percutaneous microwave ablation (PMWA) are now being performed in patients deemed "medically inoperable" with non-small cell lung cancer (NSCLC). The majority of these patients are treated without ground truth histology, relying on imaging to establish the diagnosis. The purpose of this study was to investigate whether there were differences in the visible imaging features including CT Texture Analysis (CTTA) between patients referred for surgery, SABR and PMWA, which might suggest differences in underlying diagnosis. Methods: 92 patients with one pulmonary nodule (PN) suspected as T1N0M0 to T2AN0M0 NSCLC on imaging were treated either with SABR (22 patients), PMWA (25) or Video-assisted thorascopic surgery (45) of which 23 had NSCLC (SURG M) and 22 had benign disease (SURG B). Patient characteristics, CT nodule morphology, presence of emphysema and percentage emphysema score, FDG avidity and CT textural features were compared. Twenty texture features (previously used in combination to create a nodule probability of malignancy score between 0–1) were extracted from each automatic contoured region surrounding the PN. The Kruskal-Wallis test was used to compare texture features between the 4 patient groups (SABR, PMWA, SURG M and SURG B). Results: There was no significant difference in nodule morphology, volume at presentation (p=0.280) or volume doubling times (p=0.149), and presence of emphysema (p=0.348) or emphysema score (p=0.367) between the 4 groups. There was no statistical difference in CTTA malignancy prediction score between the SABR, PMWA and SURG M groups (p≥0.05). The probability of malignancy score was significantly lower (p-value<0.01) for SURG B (0.58 mean ±0.19 sd) vs. SABR (0.79±0.15) treatment groups (figure 1 ). Conclusion: This is the first study to our knowledge to evaluate the radiological differences between patient groups referred for surgical and non-surgical treatments for NSCLC. On this small study, the Results support the hypothesis that the non-operative patient groups comprise the same proportion of benign and malignant as those in the operative group. The Results also demonstrate the potential clinical utility of CTTA in patient selection when histology is not obtainable. CTTA does not require volumetry detectable growth to detect change, and therefore may be a useful biomarker of malignancy at first diagnosis.